PERANCANGAN POWERTRAIN PADA SEGWAY - Agustinus Purna Irawan; Danardono Agus Sumarsono (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: Segway is a personal vehicle with a battery power source which is driven by an electric motor. In designing the Segway, powertrain system design includes power, resources, transmission, steering, braking system and final drives. In the design and results of field tests performed, it was shown that the powertrain system segway is very good.